2009
DOI: 10.1364/josaa.26.001202
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the simulated real-world optic flow motion aftereffect

Abstract: the aftereffect was selective for global optical flow rate, suggesting that the aftereffect reflects gain changes at processing levels where a sense of self-motion is generated. RESULTS were used in a computational model of this MAE, which was a modified framework by van de Grind et al. [Vision Res.44, 2269 (2004)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In particular, we examined whether sustained exposure to a visual self-motion stimulus (i.e., optic flow) induces a subsequent bias in nonvisual (i.e., vestibular) self-motion perception in the opposite direction in darkness. Although several previous studies have investigated self-motion aftereffects [3][4][5][6], none have demonstrated crossmodal transfer, which is the strongest proof that the adapted mechanisms are generalized for self-motion processing. The crossmodal aftereffect was quantified using a motion-nulling procedure in which observers were physically translated on a motion platform to find the movement required to cancel the visually induced aftereffect.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…In particular, we examined whether sustained exposure to a visual self-motion stimulus (i.e., optic flow) induces a subsequent bias in nonvisual (i.e., vestibular) self-motion perception in the opposite direction in darkness. Although several previous studies have investigated self-motion aftereffects [3][4][5][6], none have demonstrated crossmodal transfer, which is the strongest proof that the adapted mechanisms are generalized for self-motion processing. The crossmodal aftereffect was quantified using a motion-nulling procedure in which observers were physically translated on a motion platform to find the movement required to cancel the visually induced aftereffect.…”
mentioning
confidence: 88%
“…In particular, rigorous quantitative characterization of visual motion aftereffects has provided important clues about the neurophysiological and computational mechanisms that underlie visual motion processing [16][17][18]. Because visual motion is a dominant cue to self-motion, and because of compelling demonstrations of visual aftereffects particularly selective for visual self-motion stimuli (e.g., expanding and contracting optic flow [19][20][21]), the question has previously been raised about the possibility of analogous aftereffects for self-motion perception [3][4][5][6]. Prior studies have examined self-motion aftereffects in response to both visual [3,5,6] and vestibular [4,[22][23][24] stimuli.…”
Section: Self-motion Aftereffectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression for the leaky integrator is a first-order linear differential equation (Patterson, Tripp, Rogers, & Boydstun, 2009):…”
Section: Vigilance Decrementmentioning
confidence: 99%